Outcomes of patients with blunt chest trauma encountered at emergency department and possible risk factors affecting mortality - Yuan-Ming Tsai; Kuan-Hsun Lin; Tsai-Wang Huang; Chun-Ying Chen; Zhi-Jie Hong; Sheng-Der Hsu (Journal of Medical Sciences, 2017)
Background: Blunt chest trauma is associated with a high risk of mortality. Respiratory complications may necessitate prolonged ventilation and result in death. The present study aimed to investigate possible signs of trauma and the prognosis of trauma patients with thoracic injuries and identify risk factors for mortality. Patients and Methods: A retrospective study was performed to investigate the clinical characteristics and treatment outcomes of trauma patients with blunt chest injuries who underwent thoracic computed tomography on arrival in the emergency department (January 2010–December 2013). Patients with brain injuries were excluded from the study. The prognostic values of age, sex, trauma type, injury severity score, revised trauma score (RTS), ventilator requirement, days in Intensive Care Unit (ICU), associated thoracic injury, and laboratory examinations (including arterial blood gas [ABG]) were evaluated. Results: Fifteen of 30 analyzed patients died during their ICU stays; accordingly, we classified patients as survivors and nonsurvivors. These groups differed significantly regarding the RTS (P = 0.002), mechanical ventilation requirement (P = 0.007), total stay length (P = 0.009), and the presence of hemothorax (P = 0.030). However, no significant differences in the pneumothorax, rib fractures, and blood tests (including ABG analysis) were observed between the groups. Conclusion: Among hospitalized trauma patients with blunt thoracic injuries, RTS, mechanical ventilation requirement, and hemothorax were identified as risk factors for mortality. Patients with hemothorax should receive multidisciplinary care and be monitored closely to improve survival.